Tinggal Lebih Lama, Coping Lebih Baik? Analisis Coping Strategies Mahasiswa Asing di Universitas Airlangga: Staying Longer, Coping Better? An Analysis of Foreign Students’ Coping Strategies at Universitas Airlangga - Ajeng Diva Putri Maharani; Rania Salsabila Rahma; Lailatul Muniroh (Universitas Airlangga, 2025)
Background: Different food cultures in host countries require foreign students to adjust to the availability of food in their new environment. The duration of stay in host country may serve as a benchmark of acculturation process, particularly in relation to food access. This can be related to the coping strategies they adopt to maintain adequate levels of food security in host countries. Objectives: This study aimed to analyze the relationship between length of stay in the host country and coping strategies among foreign students at Universitas Airlangga. Methods: A cross-sectional design was used, involving 60 foreign undergraduate and postgraduate students at Universitas Airlangga, selected through accidental sampling. Data were collected using a structured questionnaire to assess students' length of stay and the Coping Strategy Index (CSI) to evaluates coping levels. The data were analyzed using the chi-square test with the SPSS software. Results: The majority of foreign students had lived in Surabaya, Indonesia, for 6-10 months (50%) and had a coping strategy scores classified as insufficient (18) (51.7%). Statistical analysis showed no significant relationship between length of stay in the host country and coping strategies among foreign students at Universitas Airlangga (p-value = 0,763). Conclusions: A longer duration of stay in Surabaya, Indonesia, does not necessarily equip foreign students with adequate coping strategies to maintain food security. These outcomes are likely influenced by individual characteristics, social networks, and environmental factors. Keywords: Length of Stay, Coping Strategy, Foreign Student